488 INTERNATIONAL HEALTH EDUCATION: MOVING MEDICAL STUDENTS FROM PASSION TO SKILL. Issue 1 (1st January 2007) - Yeong, S. K.; Bondy, L. C.; Taylor, L.; Watchorn, A.; Chiles, J.; Baharloo, B.; Reynolds, B.; Bouchard, M.; Abedi-Moghaddam, N.; Huang, A.; Kouwenberg, J.; Virmani, D.; et al.
Abstract : Background: University of British Columbia medical students interested in international health are able to attend inspirational talks and/or join international volunteer electives with nongovernmental organizations (NGOs). However, within the university, there is a shortage of training to provide students with the skills needed to participate in international health, in particular the skills for sustainable and community based international health work. Methods: In 2005, a group of students formed The UBC Medical and Dental Students' International Health Initiative. With guidance from faculty instructors and NGOs (including Doctors Without Borders [MSF]), students started four components: skill-building workshops and three international health projects in Uganda, India, and Honduras. Workshops were designed to teach medical students the skills needed to make them effective international health workers. Projects provided opportunities for students to practice those skills, in planning, development, or implementation of the projects. All the international health projects strove to address an unmet community need, partner with a local organization in the designated country, and emphasize principles of sustainability. Results: Workshops: Two skill-building workshops were held, each led by an MSF field-worker and featuring a case study based on their real-life experiences. Presenters discussed an approach to international health challenges, such as project planning and ethical decision making. Approximately 40 students from diverse faculties, including medicine, nursing, and science, attended each workshop. Workshops were rated 8.2/10 by students. Projects: Ten medical students were involved in initiating international health projects in Honduras, Uganda, and India. Projects included conducting needs assessments, working with local organizations, and delivering public health workshops. Students expressed appreciation of the value and synergy from collaborating with students and health care providers in the local community. Conclusions: Student health professionals interested in international health care were very receptive to learning skills directly from NGOs' field-workers to apply to community-based projects overseas. Students participating in the international projects were inspired and learned from firsthand experience. It is anticipated that the blend of theoretical and practical international health training for students will create skilled future international health workers and develop beneficial partnerships in global communities.